The Effect of Social Support for Career Adaptability on Final-year Students at State University of Manado - Tiara Veronika (Universitas Muhammadiyah Banjarmasin, 2023)
This research is based on the assumption that career adaptability is very important for final year students to be able to cope with the challenges of the transition from university to work. The aim of this study is to investigate the effect of social support on career adaptability. Quantitative regression analysis tests were used as the research method. The population selected were final year students at the State University of Manado using a simple random sampling technique and a total sample of 51 students. The adaptability career scale (α = 0,90) and the social support scale (α = 0,91) were the instruments used in this study. Based on the results of the regression analysis test, there is a negative effect of social support on adaptability to work. The researchers suggest that the conditions caused by social support that are received too often will, in fact, make it more difficult for students to make decisions about their careers. Social support offers knowledge and strategies for experiencing career change. This situation is not compatible with the careers of the new economy.